2017
DOI: 10.4103/ijpsym.ijpsym_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impairment and Quality of Life in Patients with Obsessive Compulsive Disorder

Abstract: Background: This study was carried out to enumerate the level of difference in functional impairment and quality of life (QOL) in obsessive-compulsive disorder (OCD) patients and normal control group to find out the relationship among ICD functional impairment and QOL. Methodology: Thirty patients diagnosed with OCD as per International Classification of Diseases Diagnostic Criteria for Research-10 were taken for study. The control group consists of 30 normal participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Obsedantně kompulzivní porucha je doprovázena četnými omezeními v osobním a mezilidském fungování (4). Snižuje kvalitu života (5-7) a vede ke zhoršení v oblastech mezilidských vztahů a profesního postavení (8). Často mívá závažný, invalidizující průběh (9,10).…”
Section: úVodunclassified
“…Obsedantně kompulzivní porucha je doprovázena četnými omezeními v osobním a mezilidském fungování (4). Snižuje kvalitu života (5-7) a vede ke zhoršení v oblastech mezilidských vztahů a profesního postavení (8). Často mívá závažný, invalidizující průběh (9,10).…”
Section: úVodunclassified
“…New studies have shown a 4-14% prevalence rate among Patients with OCD. (10,11) Considering the clinical importance, high prevalence, and high disability rates, new diagnostic and therapeutic approaches, and lack of previous studies in different cultures about delusional OCD, this study was designed to determine the frequency of this condition, specify various types of delusions and other psychotic experiences in patients with OCD, and identify the demographic and clinical characteristics of these patients. Previous studies have mainly focused on delusion and lack of insight; however, this study focused on other positive or negative psychotic symptoms too.…”
Section: Introductionmentioning
confidence: 99%
“…bsessive-Compulsive Disorder (OCD) is a disabling neuropsychiatric condition with very serious impairments and prevalence of 1%-3% [1,2]. Studies indicated an association between OCD and various functional impairments and decreased quality of life [3]. OCD could lead to functional impairments in multiple ways [4]; it has adverse consequences, such as personal, interpersonal, and quality of life problems for patients [5,6].…”
Section: Introductionmentioning
confidence: 99%